MODERNITY, LOCALITY, AND POSTCOLONIALITY OF VILLAGERS IN THE 80S - Ikwan Setiawan (Faculty of Humanities, Jember University, 2011)
Being modern in local sphere at the 80s was a complicated process. Local societies experienced and dreamed modern cultures as the dominant discursive formation caused by Green Revolution, but they still believed and practiced traditional cultures. The New Order regime’s developmentalism policy resulted socio-cultural shifting and change in both cities and villages. This article, by combining cultural studies and postcolonial studies, discusses genealogy of socio-cultural shifting and change in a village at the 80s when modern cultures came into peasants’ life–world through public television programs, education, and industrial products. However, I see the villagers could play in-between space to appropriate some modern cultures and negotiate some traditional cultures into their daily life. The cultural in-betweenness has represented the dynamics of village postcoloniality under direction of the New Order regime and has made modernity as ideological dream for the villagers in constructing their locality. Keywords: villagers, modernity, the 80’s, locality, postcoloniality